Assessing Inclusive Education in Elementary Schools: Insight from the Merdeka Curriculum - Kusuma Wijayanti; Liftiah Liftiah; Budiyono Budiyono (AL-ISHLAH: Jurnal Pendidikan, 2025)
The implementation of inclusive education in Indonesian elementary schools, as mandated by Ministry of Education Regulation No. 48 of 2023, presents several critical challenges. This study aims to evaluate how inclusive education is being implemented within the Merdeka Curriculum, focusing on the effectiveness of accommodation services provided to students with special needs. A mixed-methods design was employed, utilizing the Context, Input, Process, and Product (CIPP) evaluation model. The research involved 43 inclusive elementary schools, with participants including 45 teachers, 24 principals, and a Disability Services Unit coordinator. Data collection methods included observations, documentation, in-depth interviews, questionnaires, and focus group discussions (FGDs). Findings reveal that the input aspect is the most suboptimal area of implementation. Only 7% of schools had teachers trained in inclusive education, 9% had accessible infrastructure, 9% employed Special Mentor Teachers, 19% received special funding allocations, 37% had modified teaching materials, and 58% implemented an adaptive curriculum. In contrast, the process component showed strong implementation, evidenced by the successful practice of differentiated learning and a supportive peer environment. The context and product dimensions were also considered satisfactory, particularly with noted improvements in the social-emotional development of students with special needs. The study highlights the urgent need for systemic improvements in the foundational resources required for inclusive education under the Merdeka Curriculum, particularly in training, infrastructure, and funding. Enhancing these inputs is essential to ensuring the long-term success and equity of inclusive educational practices.